Peran dan Strategi Kasatkorkel Banser dalam Pengembangan Keterampilan Vokasional Pemuda di Pimpinan Ranting GP Ansor Desa Sidoharjo Kecamatan Jambon - Khoirul Anam (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2026)
The development of vocational skills is one of the efforts to improve the quality of human resources, particularly among rural youth. Youth organizations play a strategic role in shaping skills, character, and independence through various empowerment and training programs. This study aims to analyze the role and strategies of the Kasatkorkel Banser of the GP Ansor Branch Leadership in Sidoharjo Village, Jambon District, in developing youth vocational skills, as well as to identify the supporting and inhibiting factors involved. This research employed a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation. The informants consisted of administrators and members of Banser GP Ansor in Sidoharjo Village. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that Banser plays a significant role in improving youth vocational skills through construction training programs, cadre development, socio-religious guidance, and the utilization of digital media as a means of organizational development. The strategies implemented include digitalization strategies and marketing strategies through the development of vocational skill-based enterprises. Supporting factors include social equality, cadre education, organizational ideology, and member loyalty, while inhibiting factors consist of economic conditions and the low educational background of the community. This study demonstrates that religion-based youth organizations contribute significantly to the development of vocational skills and the empowerment of rural communities.